Hyperparathyroidism–jaw tumor syndrome. Issue 6 (2nd February 2012) - Kutcher, Matthew R.; Rigby, Matthew H.; Bullock, Martin; Trites, Jonathan; Taylor, S. Mark; Hart, Robert D.; Andersen, Peter; Andersen, Peter
Abstract Background Hyperparathyroidism–jaw tumor (HPT‐JT) syndrome is a rare autosomal dominant multiple tumor syndrome characterized by hyperparathyroidism due to single or multiple‐gland parathyroid tumor(s). Since it was first described in 1990, the genetics underlying the syndrome have been elucidated and typical clinical presentations are becoming clarified as literature describing this rare entity amasses. Methods and Results A 22‐year‐old man presented with a 2‐year history of fatigue, weight loss, nausea, and vomiting. Anemia workup indicated severe hypercalcemia. Investigations were consistent with a diagnosis of HPT‐JT. The patient underwent a total 4‐gland parathyroidectomy with single gland reimplantation. Conclusion HPT‐JT is a complex syndrome with phenotypic manifestations that can seem physiologically and temporally unrelated. The risk of parathyroid carcinoma is elevated in patients with HPT‐JT, necessitating rapid treatment and complete tumor resection to reduce the morbidity and mortality associated with intractable hypercalcemia due to local recurrence or metastatic disease. © 2012 Wiley Periodicals, Inc. Head Neck, 2012